The state of the world : colonialism, statism and humanitarian intervention : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Strategic Studies at Massey University, New Zealand - Sim, Jeffrey Vee Ming (Massey University, 2010)
Peacekeeping and peacebuilding have been a major issue in International Relations scholarship, especially since the end of the Cold War. Once the Cold War was over, the United Nations found itself drawn into conflicts with different characteristics and for different reasons. This dissertation examines the contours of second generation peacekeeping operations from a standpoint informed by postcolonial theory and other critical theoretical perspectives. It examines the emergence of widened peacemaking and peace enforcement activities in Somalia and Haiti, and also examines alternative approaches to conflict transformation by examining networked social movement responses. In particular, it explores and expounds the postcolonial view that peacekeeping interventions silence and disempower Southern (or Third World) populations, operating as a form of crisis management. It explores the hypothesis that the duty to protest is another form of colonialism, coinciding with structural destabilisation to produce unequal power.
Keywords: Peacekeeping forces; Imperialism; Humanitarian intervention; Somalia; Haiti; Politics and government; Statism